(untitled) (Bombay Hospital Journal, 2026)
Abstract Background - Dacryocystorhinostomy (DCR) is the surgical gold standard for treating nasolacrimal duct obstruction (NLDO), creating a direct passage between the lacrimal sac and nasal cavity to restore tear drainage. Despite high success rates, failures can occur due to anatomical or functional factors. This five-year retrospective study analyses 50 DCR cases, focusing on demographics, causes of failure, intranasal pathologies, and outcomes of revision procedures with silicone intubation. Methods - A retrospective review of 50 consecutive DCR surgeries was conducted at a tertiary care centre. Data regarding demographics, surgical approach, failure causes, and associated intranasal findings such as deviated nasal septum (DNS) and adhesions were collected. Revision outcomes with silicone intubation and adjunct Mitomycin C (MMC) were also evaluated. Both adult and paediatric cases were included. Results - Among 50 patients, 45 were adults and 5 were paediatric (ages 5–11); 33 were females and 17 males. Thirty-five surgeries were left-sided and 15 right-sided, all with silicone intubation. The overall failure rate was 10% (5 cases). Three failures were related to high DNS and resolved after septoplasty; one due to intranasal adhesion was corrected endoscopically, and one was managed by nasolacrimal probing. Four revision DCRs with MMC achieved successful outcomes. Paediatric patients showed good anatomical response and recovery. Conclusion - Comprehensive nasal evaluation and ENT collaboration are essential for identifying intranasal causes of DCR failure. Silicone intubation and adjunctive MMC improve success rates, while postoperative endoscopic follow-up ensures durable results. Keywords: Dacryocystorhinostomy, deviated nasal septum, nasolacrimal duct obstruction, revision surgery, silicon tube insertion